Strikes and the National Health Service: Some legal and ethical issues. Issue 2 (June 1977) - Dworkin, Gerald
Abstract : This paper is sadly opportune. The general public is angry and bewildered if not hurt by the variety of strikes which are brought more or less forcibly to their attention. People used to understand what lay behind a strike - a demand for more pay, better conditions - but today a political element often intrudes, and it is this that worries those who ask themselves whether this or that dispute is either lawful or morally acceptable. Professor Dworkin, a lawyer, first sets out the legal issues surrounding strikes and then advances the ethical arguments, closely relating them to the legal framework. The most interesting part of the paper, however, may well be that devoted to the moral obligation of example, in particular the example to be set by members of the medical profession and by all those caring for the sick. As public attitudes to industrial disputes `become dulled and quiescent' it is absolutely necessary that there should be a reappraisal of the moral standards of the past which coincide with a respect for the law. In the last century the term `anomie' was used to describe a `society which has shaken off its former restraints such as religion, respect for law and order and a definite moral code as to what is right and wrong'. We are living in that sort of society today, and one need not be a professional `ethicist' to recognize the signs, and hopefully, to work for the return of `ethical' values.